2015
DOI: 10.1111/php.12424
|View full text |Cite
|
Sign up to set email alerts
|

Hiporfin‐Mediated Photodynamic Therapy in Preclinical Treatment of Osteosarcoma

Abstract: This study was carried out to investigate the anti-tumor effect and mechanism of hiporfin-mediated photodynamic therapy (hiporfin-PDT) in osteosarcoma. We found that hiporfin accumulated mainly in the cytoplasm of osteosarcoma cells in a time and concentration-dependent manner. Hiporfin-PDT inhibited the proliferation, induced apoptosis and produced cell cycle arrest at G2M in osteosarcoma cell lines. Hiporfin-PDT increased the expression of cleaved-caspase-3, cleaved PARP-1, Bax and RIP1 while it decreased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 40 publications
1
28
0
1
Order By: Relevance
“…In Li's research, DCFH-DA was employed to detect the level of ROS in MG-63, which caused the endoplasmic reticulum stress in mitochondrial pathway [34]. This is consistent with other conclusion of PDT on OS treatment [14, 35, 36]. However, because of the high level of metabolism, the oxygen pressure in OS tissue is lower that that in benign tumor and normal tissues, which remarkably limits the anti-tumor effect in OS PDT[37].…”
Section: Oxidative Stresssupporting
confidence: 59%
See 3 more Smart Citations
“…In Li's research, DCFH-DA was employed to detect the level of ROS in MG-63, which caused the endoplasmic reticulum stress in mitochondrial pathway [34]. This is consistent with other conclusion of PDT on OS treatment [14, 35, 36]. However, because of the high level of metabolism, the oxygen pressure in OS tissue is lower that that in benign tumor and normal tissues, which remarkably limits the anti-tumor effect in OS PDT[37].…”
Section: Oxidative Stresssupporting
confidence: 59%
“…Sun's research showed that hiporfin-PDT had an anti-tumor effect to the OS cells, inducing apoptosis and cell cycle arrest at G2/M in vitro [14]. The second generation of PSs includes meso-tetrahydroxyphenyl chlorine (mTHPC), δ-aminolevulinic acid (ALA), and the phthalocyanines.…”
Section: Photosensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the combination of a heat shock protein inhibitor with low dose SHK enhanced cell apoptosis, while high-dose SHK induced necroptosis in MM cells [142]. Moreover, hiporfin-mediated photodynamic therapy in the preclinical treatment of osteosarcoma demonstrated that cell death caused by hiporfin-PDT could be rescued by Nec-1, but not by Z-VAD-FMK [143]. Additionally, RIP3 expression induced death profile changes in U2OS osteosarcoma cells after 5-aminolevulic acid (5-ALA)-mediated photodynamic therapy (PDT), suggesting that autophagy was likely to play a protective role against PDT-induced cell death and allow better survival for RIP3-U2OS cells [144].…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%